Gender Age Disparity in Amoebiasis Prevalence in Iraq: Perbedaan Usia Jenis Kelamin dalam Prevalensi Amoebiasis di Irak - Qasim Ibrahim Khalaf (Universitas Muhammadiyah Sidoarjo, 2024)
This comparative cross-sectional study evaluates the prevalence of Entamoeba histolytica, the causative agent of amoebiasis, in the human population of Diyala Governorate, conducted at Alshams Medical Labs in Baqubah city. Despite the global health burden of amoebiasis, particularly in developing countries, data on its age and gender-specific prevalence remain sparse. Aimed at filling this knowledge gap, our research specifically assessed the distribution of E. histolytica in males and females across two age groups (1-15 years and 15-45 years). The study found that 74% of females aged 1-15 years harbored both cysts and trophozoites, while males of the same age group showed a markedly lower prevalence at 19%. In the 15-45 year age group, males demonstrated a higher prevalence (50%) compared to females (9%). These findings suggest significant gender and age-related disparities in the prevalence of E. histolytica. The results could inform targeted public health interventions and contribute to more effective management and prevention strategies for amoebiasis in endemic regions. Highlights: Gender Disparity: Marked differences in infection rates between males and females. Age Influence: Varied prevalence across different age groups. Health Strategy Needs: Highlights the necessity for targeted public health interventions. Keywords: Amoebiasis, Entamoeba Histolytica, Prevalence, Gender Disparity